Asuhan Keperawatan Maternitas Pada Ny. T Pasca Sectio Caesarea Dengan Penerapan Teknik Relaksasi Benson Untuk Mengurangi Masalah Keperawatan Nyeri Di Rumah Sakit Harapan Bunda Kota Batam - Lis Kartiksari; Nelli Roza (Journal of Educational Innovation and Public Health, 2026)
Sectio caesarea is a common surgical procedure to deliver a baby when normal delivery is not possible or risky. Postoperatively, patients often experience acute pain that can interfere with the recovery process. The benson relaxation technique is a nonpharmacological method that has been shown to be effective in reducing pain through a relaxation and patient confidence approach. This study uses a case study approach on Mrs. T, a post-sectio caesarea patient at Harapan Bunda Hospital, Batam City. Nursing care is carried out comprehensively for three days, including assessment, diagnosis, intervention, implementation, and evaluation. The main intervention was the administration of benzone relaxation techniques for 10–15 minutes every day. After three days of applying the Benson relaxation technique, Mrs. T's pain intensity decreased from a scale of 6 (moderate pain) to a scale of 2 (mild pain). Patients show increased comfort, ability to be active, and decreased expressions of pain such as grimacing. These results support previous findings that benzon relaxation is effective as a nonpharmacological therapy in reducing postoperative pain. This technique can be a safe and easy-to-apply alternative in nursing practice, especially for post-sectio caesarean patients.